ANALYSIS OF SHIPBUILDING BUSINESS DEVELOPMENT STRATEGY IN BATANG PORT WITH PEST AND FIVE PORTER APPROACH - Satrio, Danang; Muhardono, Ari; Firmansyah, M. Adi; Achmad Darodjat, Tubagus (Penerbit Lafadz Jaya, 2024)
This study analyzes the development strategy of the Karangasem shipbuilding business using the PEST (Political, Economic, Social, Technological) and Porter’s Five Forces frameworks. The Covid-19 pandemic significantly impacted the shipbuilding industry, leading to disruptions in licensing, decreased orders, and reduced workforce numbers. Changes in governmental policies have shifted ship legality from regional to central authorities, exacerbating production challenges. Entrepreneurs often built ships without confirmed orders (Idle Stock), increasing operational costs and causing financial strain due to raw material wastage and labor expenses. This research employs a descriptive qualitative method to evaluate internal and external business environments using the PEST and Porter’s Five Forces frameworks. The results indicate intense competition among similar industries, high production costs, and challenges from new entrants influenced by government policies. Recommendations include strategic improvements through differentiation, cost management, and leveraging supportive relationships with suppliers and regulators.